THE HOMONYMIC PROPERTIES OF PHRASEOLOGICAL UNITS IN UZBEK AND TURKISH LANGUAGES - S.B.Khursankulov; D.Z.Abduazimova (TADQIQOTLAR, 2026)
Abstract:This article presents a comparative analysis of the homonymic features of phraseological units in the Uzbek and Turkish languages. The study identifies the semantic, structural, and functional characteristics of phraseological homonyms and highlights their patterns of use in speech. Within the scope of this brief research, phraseological units that are identical in form in both languages but differ in meaning are examined through illustrative examples. The findings of the study contribute to a deeper understanding of Turkic phraseology and are of significant importance for translation theory as well as for comparative approaches in linguistics.